Value and abstraction in Marx's Capital. Issue 2 (3rd April 2019) - Psillos, Stathis
Abstract : The main thesis of this paper is the following: Already in his Critique of Political Economy in 1859 and more forcefully in Capital in 1867, Marx relies on two distinct kinds of abstraction in order to introduce and explain Value. The first kind of abstraction – which I call abstraction1 or 'Aristotelian abstraction' – takes it that two (or more) actual commodities, despite their vast difference ('atom for atom') in their concrete material individuality, can contain the same quantity of Abstract General Labour (AGL). The second kind of abstraction – abstraction2 – is of substantially different form: it replies on an abstraction principle which introduces Value on the basis of an equivalence relation that is defined on commodities qua concrete material entities (what he calls 'use-values'), which however contain the same amount of AGL. This second kind of abstraction allows him to perform a path-breaking move in the theory of value, viz., to introduce a new sort of (abstract) entity (Value) which he implicitly defines by means of reconceptualisation of the content of statements which capture an equivalence relation among, ultimately, concrete commodities (use-values), which, however, contain the same amount of AGL.